Al-Ghazali's Theory of Real Knowledge: An Exploration of Knowledge Integration in Islamic Epistemology through Contemporary Perspectives - Aminullah Poya; Habiburrahman Rizapoor (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Abstract This research aims to explore Al-Ghazali's theory of real knowledge and elucidate the concept of knowledge and its integration features in grounding Islamic knowledge according to the contemporary theories of epistemology. The study delves into Al-Ghazali's perspectives on knowledge, analyzing and interpreting them in light of modern knowledge theories. The research finds that the cognitive integration features in Al-Ghazali's philosophy lie in the integration of knowledge sources, methods, sciences, and scholars. This is achieved through a comprehensive review of some of Al-Ghazali's works, as well as relevant studies, books, and research about his contributions to Islamic epistemology. Al-Ghazali encourages scholars to collaborate and integrate their knowledge to attain true understanding, a principle evident in this research through the exploration of modern epistemological concepts. The research utilized both inductive and descriptive methods to identify the characteristics of knowledge and demonstrate its integration aspects in Al-Ghazali's teachings. The research is structured into an introduction and three main sections: the first section introduces Al-Ghazali and his era, the second section explores the concept of knowledge and its integration in Islamic epistemology according to Al-Ghazali, and the third section examines knowledge sources, methods, types of knowledge, and scholars in Al-Ghazali's philosophy.